2014
DOI: 10.1021/jp504527b
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Charge Carriers on Radial Zinc Oxide and the Study of Their Stability and Dielectric Behavior in Poly(vinylidene fluoride)

Abstract: Radial zinc oxide (ZnO) was prepared using a new user-friendly chemical process, and the surface was modified by adsorbing polyaniline (PANI) as a charge carrier. The modified ZnO (PZnO) was used to prepare poly(vinylidene fluoride) (PVDF)–PZnO nanocomposites with improved dielectric properties. The structural morphology of the fillers was examined using powder X-ray diffraction and then correlated with observations from high-resolution transmission electron microscopy. A new characterization technique was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…Aepuru et al reported a user-friendly chemical process for the preparation of the filler that resulted in stable fillers in polymers and enhanced the dielectric properties of the composite at different frequencies and temperatures. They modified ZnO with polyaniline (PANI) as an interface in ZnO and used the PANI modified ZnO as fillers in PVDF [ 36 ].…”
Section: Polymer Based Substratesmentioning
confidence: 99%
“…Aepuru et al reported a user-friendly chemical process for the preparation of the filler that resulted in stable fillers in polymers and enhanced the dielectric properties of the composite at different frequencies and temperatures. They modified ZnO with polyaniline (PANI) as an interface in ZnO and used the PANI modified ZnO as fillers in PVDF [ 36 ].…”
Section: Polymer Based Substratesmentioning
confidence: 99%
“…[17] There have also been some researchers who have used ZnO as fillers to dope PVDF. [8,18] These studies confirmed that ZnO can significantly enhance the dielectric properties of the material.…”
Section: Introductionmentioning
confidence: 53%
“…However, the volume fraction of ceramics is required to be no less than 0.50. [8,18] These studies confirmed that ZnO can significantly enhance the dielectric properties of the material. [12] Lee et al [13,14] filled treated BaTiO 3 with PVDF.…”
Section: Introductionmentioning
confidence: 69%
“…Moreover, the EPR signal intensity increased significantly in the spectra of PCN1 and PCN0 compared to that of CN, which suggests a higher unpaired electron spin density. The number of charge carriers is related directly to material conductivity and is obtained from Equation : trueNc=(σ/ρeμ) …”
Section: Resultsmentioning
confidence: 99%